Effect of polymer types on metal oxide substrates as an EGFET sensor-based nitrate sensing layers / Shaiful Bakhtiar Hashim ... [et al.] - Hashim, Shaiful Bakhtiar; Rosli, Aimi Bazilah; Zulkifli, Zurita; Abdullah, Wan Fazlida Hanim; Herman, Sukreen Hana (UiTM Press, 2022)
The effect of polymer-based sensing electrodes on the detection of nitrate was presented in this paper. Polyvinyl butyral (PVB) and Polyvinylpyrrolidone (PVP) were employed as the nitrate sensing layers of the Extended Gate Field Effect Transistor (EGFET), which was fabricated on different metal oxide substrates, namely Tantalum Pentoxide (Ta2O5) and Indium Titanium oxide (ITO). The sensing electrode was connected to the gate of CD4007 commercial MOSFET. The spin coating technique was used to deposit the polymer concentration at 3000 rpm for 30 seconds for each sample. The samples were characterized to obtain the linearity and sensitivity of the sensing electrode from three different nitrate concentrations (0, 50 and 100 ppm). Ta2O5 shows a higher sensitivity for the metal oxide substrate than the ITO, with 7.2 mV/dec for ITO and 14.5 mV/dec for Ta2O5. The study has proved that the deposition of polymers on the sensing electrode improved sensitivity and linearity. The PVB on ITO and Ta2O5 shows the sensitivity and linearity of 40.9 mV/dec and 0.9994 and 36.9 mV/dec and 0.3832, respectively. It shows that the nitrate sensing performance of the ITO sensing electrode improved almost six times when PVB polymer was used as a composite layer. While the use of PVB polymer on top of the Ta2O5 sensing layer improved the sensitivity values by approximately three times than sensitivity value obtained using bare Ta2O5. In contrast, the sensitivity for PVP demonstrates 24.4 mV/dec and 36.3 mV/dec, with an increment of 68% and 404% on Ta2O5 and ITO, respectively. The linearity shows 0.8713 for Ta2O5 and 0.5723 for ITO. Thus, PVP is better on Ta2O5, and PVB is better on ITO substrate. Both conditions are significant in improving the sensitivity of the sensing electrode.